(untitled) (Applied Biological Research, 2025)
Diabetes is globally one of the leading non-communicable diseases that pose significant public health challenges. The Potassium Inwardly Rectifying Channel Subfamily J Member 11 (KCNJ11) gene polymorphism has been implicated in beta-cell dysfunction and altered insulin secretion through potassium-gated channels, potentially influencing type 2 diabetes mellitus (T2DM) susceptibility. Genotyping was performed using restriction fragment length polymorphism, with verification through Sanger Sequencing. The association between KCNJ11 genotypes and T2DM risk was evaluated using odds ratios and confidence intervals. Biochemical and clinical variables were compared between patients and controls using Student’s t-test and Chi-square (χ²) tests. Statistical analysis was conducted using SPSS software. The frequency distribution of KCNJ11 (rs5210) SNP (A/G) differed significantly between the control group and T2DM patients (X² = 31.7). The dominant genetic model (p value